Bahan ajar persamaan diferensial berbasis higher order thinking skills - Nurul Arfinanti (Department of Mathematics Education, UIN Sunan Gunung Djati Bandung, West Java, Indonesia, 2020)
The purpose of this research is to produce teaching materials for differential equations based on higher-order thinking skills. HOTS training for prospective teachers is important so that they can train it also for students. This research is a development study and uses a development research procedure revealed by Thiagarajan, namely 4D (Define, Design, Development, and Disseminate). Data collection instruments used consisted of expert validation sheets, student response sheets, and test questions. The results of the study show that HOTS-based Differential Equation courses have been well developed and meet minimum standards of quality of teaching materials. The assessment of the three experts obtained the percentage of ideals of the average score of 91.66%, which is in the very good category. At the same time, the response of students to teaching materials gained a percentage of ideals 75.89%, which is in the very good category.